The politics of protracted accommodation: State welfare and denotified, nomadic tribes in India - Patil, Dhanraj A. (IASSI Quarterly: Contributions to Indian Social Science)
The denotified, nomadic and semi-nomadic tribes (DTNT & SNT$1 (Bs) are one of the most subjugated groups of Indian society. Due to the historic injustice as roofed as delinquent subjects they continue to remain at the periphery of development and struggling for their constitutional right to justice, equality and freedom. This paper attempts to explore few intricate questions for instance: Why are they not accommodated and represented adequately as legitimate citizens of democracy? And Are they victims of the politics of accommodation and the targets of developmental governmentality? To investigate the research problem under investigation the paper applies critical discourse-method and (3z(Bpolitics of accommodation and governmentatility(3y (Bas prime methodological and theoretical foundations. The paper concludes that (DTNT & SNT$1 (Bs) have become the hapless-victims of the politics of accommodation since colonial-period and the post colonial state also failed to ecolonize this false construction, tactically. The paper suggest that, the meaningful accommodation of (DTNT & SNT$1 (Bs) in the democratic structures is intuitively centred on i) how state and the larger society build necessary and sufficient conditions and ii) time bound strategic action framework and rightful dialog with democratic and political institutions upon whom the onus lies for the welfare of historically disenfranchised communities. - Reproduced s
Keywords: Nomadic tribes, Politics of accommodation, Governmentality, Welfare, India